Digital Transformation: Strengthening Financial Literacy and QRIS Payment Technology for Traditional Traders Associations in Argosari Market Gunungkidul - Nuraini, Anisa; Rahmadhani, Anisa Nur; Raharjanti, Rachel Rinukti; Susanti, Leli; Transistari, Ralina (Society : Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology in Indonesia presents challenges for the Argosari Traditional Market Traders Association in Gunungkidul. These challenges arise from low levels of financial literacy, as the association has not yet implemented simple digital financial record-keeping on a regular basis or adopted QRIS digital payment technology. The purpose of this activity was to strengthen the association’s understanding and skills in simple digital financial record-keeping and the use of QRIS payment technology. The PKM-PM implementation method consisted of three stages. The socialization stage involved providing materials and modules to give an initial overview of the importance of financial literacy and the use of QRIS payment technology. The training stage involved direct assistance, including guidance in financial record-keeping using Microsoft Excel and the use of QRIS payment technology through the GoPay Merchant application. The evaluation stage included analysis of pre-test and post-test results, while monitoring was conducted through direct interviews two weeks after the program ended to assess its sustainability. This activity was carried out from July to November 2025 with community partners comprising 20 market traders. The results showed an increase in the community’s understanding of simple digital financial record-keeping, with the average score rising from 83 to 92.5, and in the use of QRIS payment technology, from 84 to 91. The improvement in the community’s skills was demonstrated by traders implementing both simple digital financial record-keeping and QRIS payment technology in their daily business operations.    Perkembangan teknologi digital di Indonesia telah menjadi tantangan bagi Paguyuban Pedagang Pasar Tradisional Argosari, Gunungkidul. Hal ini disebabkan oleh rendahnya tingkat literasi keuangan, dimana paguyuban belum melakukan pencatatan keuangan sederhana secara digital dan rutin, serta belum menerapkan teknologi pembayaran digital QRIS. Tujuan kegiatan ini adalah untuk menguatkan pemahaman dan keterampilan paguyuban dalam pencatatan keuangan digital sederhana serta penggunaan teknologi pembayaran QRIS. Metode pelaksanaan PKM-PM mencakup tiga tahapan. Tahapan sosialisasi dilakukan melalui pemberian materi dan modul untuk memberikan gambaran awal mengenai pentingnya literasi keuangan dan pemanfaatan teknologi pembayaran QRIS. Tahap pelatihan dilakukan melalui pendampingan langsung, yang meliputi pelatihan pencatatan keuangan menggunakan Microsoft Excel dan penggunaan teknologi pembayaran QRIS melalui aplikasi GoPay Merchant. Tahap evaluasi dilakukan dengan menganalisis hasil pre-test dan post-test, sedangkan monitoring dilakukan melalui wawancara langsung dua minggu setelah program selesai untuk menilai keberlanjutan program. Kegiatan ini dilaksanakan dari bulan Juli hingga November 2025 dengan melibatkan 20 pedagang sebagai mitra paguyuban. Hasil kegiatan menunjukkan adanya peningkatan pemahaman paguyuban terhadap pencatatan keuangan digital sederhana dengan nilai rata-rata meningkat dari 83 menjadi 92,5, serta peningkatan pemanfaatan teknologi pembayaran QRIS dari 84 menjadi 91. Peningkatan keterampilan paguyuban ditunjukkan dengan telah diterapkannya pencatatan keuangan digital sederhana dan penggunaan teknologi pembayaran QRIS oleh para pedagang dalam kegiatan usahanya.